Exploring Audience Perspectives on Self-Development and Career Growth Through YouTube Comments: Evidence from the SUARA BERKELAS Podcast - Andi Nurfiana Haz; Chairunnisaa M Z Huzaen (PT Maju Malaqbi Makkarana, 2026)
The growth of digital media has transformed the way individuals access information, share experiences, and engage in discussions related to self-development and career growth. Among various digital platforms, YouTube podcasts have emerged as popular sources of informal learning and personal reflection. This study explored audience perspectives on self-development and career growth through comments posted on the SUARA BERKELAS podcast on YouTube. The data consisted of 704 audience comments collected using a web scraping technique. Text preprocessing was conducted through case folding, cleaning, tokenization, and stopword removal. Subsequently, bigram analysis and Latent Dirichlet Allocation (LDA) topic modeling were applied to identify dominant discussion themes. The findings reveal five major themes: social reflection and national issues, life aspirations and future goals, youth self-development, motivation and life struggles, and concerns about the future. These themes indicate that audiences perceive the podcast not only as a source of entertainment but also as a medium for learning, self-reflection, and career development. The coherence score of 0.44 suggests that the topic model demonstrates acceptable consistency in representing audience discussions. This study highlights the role of digital podcasts in shaping audience perspectives on personal growth and career-related issues in contemporary society.